The Relationship between HIV Co-Infection and The Risk of Developing Drug-Resistant Tuberculosis (DR-TB) : A Systematic Review - Elis Nurhasanah; Teguh Budi Santosa; Yusifa Elfiani (The International Journal of Medical Science and Health Research, 2026)
Introduction: The dual epidemics of HIV and tuberculosis (TB) present a major global health challenge, with drug-resistant TB (DR-TB) being a critical concern. While HIV is known to increase the risk of active TB, its precise role in the development of drug resistance remains debated due to heterogeneous findings. This systematic review aims to synthesize global evidence on the association between HIV co-infection and the risk of developing drug-resistant tuberculosis. Methods: We conducted a systematic review of studies published up to 2025. We screened for observational studies that included active TB patients, reported HIV status, and assessed drug resistance. Data on study characteristics, HIV assessment, DR-TB definition, and measures of association were extracted. Findings were synthesized narratively, focusing on overall association, resistance type (primary vs. acquired), and the role of antiretroviral therapy (ART). Results: A total of 200 studies were included,. Meta-analyses consistently showed a positive association between HIV and DR-TB, with pooled odds ratios for multidrug-resistant TB (MDR-TB) ranging from 1.42 (95% CI: 1.17-1.71) to 1.47 (95% CI: 1.19-1.81). The association was significantly stronger for primary MDR-TB (OR up to 3.13) than for acquired resistance. Antiretroviral therapy (ART) was strongly protective; HIV-positive patients on ART had significantly lower mortality (OR 1.8, 95% CI: 1.5-2.2) compared to those not on ART (OR 4.2, 95% CI: 3.0-5.9). Low CD4 count (<200 cells/mm³) was a critical risk factor for both acquiring resistance and poor treatment outcomes. Previous TB treatment history was a major confounder, showing a strong independent association with DR-TB (AOR up to 83.8). Discussion: HIV co-infection increases the risk of DR-TB, particularly primary resistance, likely due to increased susceptibility to infection and rapid progression. The strong protective effect of ART highlights immune reconstitution as a key mechanism. The association is context-dependent, modified by background TB epidemiology, healthcare systems, and survival bias. Conclusion: HIV is a significant risk factor for DR-TB, with the strongest evidence for primary resistance. Early ART initiation and integrated TB-HIV care are crucial for mitigating this risk. Future research should focus on acquired resistance, optimized dosing, and interventions to address social determinants of health.